Dimensionality and Defect Engineering Using Fluoroaromatic Cations for Efficiency and Stability Enhancement in 3D/2D Perovskite Photovoltaics. Issue 3 (21st December 2020) - Lee, Hock Beng; Kumar, Neetesh; Tyagi, Barkha; Ko, Keum-Jin; Kang, Jae-Wook
Abstract : State‐of‐the‐art perovskite solar cells (PSCs) based on three‐dimensional (3D) films have achieved high power conversion efficiencies (PCEs), but are relatively fragile in high‐temperature and humid environments. This shortcoming must be addressed before PSCs can be fully commercialized. Herein, the use of a fluorinated aromatic organic spacer cation, 4‐fluoro‐phenethylammonium iodide (FPEAI), to fine‐tune the dimensionality and surface morphology of perovskite films is demonstrated. Surface treatment with FPEAI can lead to in situ formation of a two‐dimensional (2D) (FPEA)2 PbI4 perovskite capping layer atop a 3D perovskite film, producing novel 3D/2D interface in perovskite films. Simultaneously, FPEAI treatment can induce a novel grain‐boundary passivation effect on the film surface, which helps to suppress undesirable charge recombination. After FPEAI treatment, standard (0.09 cm 2 ) and large‐area (2.00 cm 2 ) PSCs achieve PCEs of 20.53% and 16.82%, respectively. The FPEAI‐treated PSCs also demonstrate superior air‐ and photo‐stability due to the hydrophobic (FPEA)2 PbI4 capping layer that reduces moisture ingress into perovskite structures. Furthermore, a 11.2 cm 2 large FPEAI‐treated PSC module with a PCE of 13.66% are successfully fabricated. FPEAI passivation is a facile strategy to produce 3D/2D multi‐dimensional PSCs with superior performance and stability. Abstract : The dimensionality, optoelectronic properties, and stability of lead halide perovskite films can be fine‐tuned via surface passivation with bulky fluoroaromatic cations. This study demonstrates the practical use of fluorinated phenethylammonium iodide (FPEAI) for simultaneous efficiency and stability improvement in large‐area perovskite solar cell devices and modules.